2000
DOI: 10.1590/s1516-89132000000100014
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the floral biology and reproductive system of Brassica napus L.(Cruciferae)

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 5 publications
(4 reference statements)
1
22
0
1
Order By: Relevance
“…Diverging results were found in tests developed by Mussury and Fernandes (2000) in the municipality of Dourados, Brazil, with cultivar CTC-4, and by Delaplane and Mayer (2000), in Georgia, USA, in which they concluded that, when the flower opens, its stigma is already receptive but the anthers are not yet dehiscent, verifying protogyny in the flowers. These two authors state that, within the studied cultivars, anther dehiscence occurs after the complete opening of the flower.…”
Section: Anthesis and Stigma Receptivitymentioning
confidence: 97%
See 2 more Smart Citations
“…Diverging results were found in tests developed by Mussury and Fernandes (2000) in the municipality of Dourados, Brazil, with cultivar CTC-4, and by Delaplane and Mayer (2000), in Georgia, USA, in which they concluded that, when the flower opens, its stigma is already receptive but the anthers are not yet dehiscent, verifying protogyny in the flowers. These two authors state that, within the studied cultivars, anther dehiscence occurs after the complete opening of the flower.…”
Section: Anthesis and Stigma Receptivitymentioning
confidence: 97%
“…B. napus flowers are extremely attractive to them (Abrol, 2007) and its high level of attractiveness is related to its fragrance (Mussury and Fernandes, 2000) and to its abundant food resources (Williams, 1980;Mesquida et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…De acordo com Mussury & Fernandes (2000), a ocorrência da alogamia é freqüente em condições naturais, em razão da alta população de polinizadores em determinados períodos, favorecendo o desenvolvimento de plantas com maior tamanho de frutos e maior número de sementes. Para Kevan & Eisikowitch (1990), a presença dos polinizadores aumenta a germinação das sementes de B. napus de 83% para 96%.…”
Section: Introductionunclassified
“…Other rapeseed cultivars have been reported to show different anthesis periods. For example, CTC-4 has been reported by different authors to exhibit an anthesis period of 32.5 ± 8.6 hours (Adegas and Nogueira Couto, 1992) or 48 hours (Mussury and Fernandes, 2000), and Hyola 432 shows an anthesis period of 72 hours (Rosa et al, 2010).…”
Section: Discussionmentioning
confidence: 99%